FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN UMKM: PENDEKATAN KUALITATIF MELALUI KAJIAN PUSTAKA - Sadiqin, Amin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The quality of financial reporting among SMEs in Indonesia remains a fundamental challenge affecting financing access and business sustainability. This study aims to identify and analyze factors influencing SME financial reporting quality through a qualitative approach using systematic literature review. Library research method was employed to analyze national and international literature from 2020-2025 using content analysis and thematic analysis techniques. Results indicate that SME financial reporting quality is influenced by complex interactions of internal organizational factors including owner characteristics, human resource capabilities, and technological infrastructure, as well as external factors comprising government regulations, stakeholder pressures, and ecosystem support. Information technology serves as an enabler and moderator strengthened by human resource competency. The research produces an integrated framework demonstrating the need for holistic approaches in improving SME financial reporting quality. Practical implications include the importance of human resource capacity development, accounting information system implementation, and comprehensive regulatory support to achieve quality financial reporting.